Buffer Solution: Multiculturalism and the Mourning of Intra-Ethnic Diversity in Homeland Elegies - Ansari, Farrah (Annals of Human and Social Sciences, 2024)
This paper scrutinizes the intricate dynamics between multiculturalism and minority ethnic communities, particularly emphasizing multiculturalism’s failure to address intra-ethnic diversity. This claim is unpacked through the textual and character analysis of Ayad Akhtar’s novel, Homeland Elegies. By analyzing the experiences of four Pakistani American characters in the novel, the study argues that the broad labels such as "Muslim" and "Pakistani Muslim" obscure distinct heterogeneous identities within one ethnic identity. By taking aid from the theoretical concepts of Mondal’s "multiculturalism as a divisive and devastating failure," Madood’s "additive rather than subtractive multiculturalism," “interculturalism as a distinctive alternative to multiculturalism,” and Hegelian "intersubjective recognition," this study aims to demonstrate the role of multiculturalism in erosion and distortion of minority ethnic identities. By focusing on the experiences of all Pakistani American characters, this study recommends adopting a nuanced multicultural approach that acknowledges and inclusively represents intra-ethnic diversity to prevent the distortion and erosion of minority ethnic identities